Gaya Kepemimpinan Otoriter Terhadap Stres Kerja - Rafifa Najla Amalia; Ghina Salsabila Daulay; Aos Kuswandi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Work stress is a physical and mental response of individuals to environmental changes that induce anxiety. Suboptimal employee performance is often caused by ineffective leadership styles, particularly authoritarian leadership. Authoritarian leaders tend to view the organization as their personal property, exhibit arrogance, and are reluctant to accept criticism, resulting in a lack of employee involvement in decision-making. This study analyzes the impact of authoritarian leadership on employee work stress levels through a literature review of national research articles published between 2014 and 2024. The findings indicate that authoritarian leadership has a positive and significant effect on work stress, as leaders take over all decision-making, leaving subordinates to merely execute assigned tasks without participation, which can trigger stress.